2020
DOI: 10.22270/jddt.v10i2.3923
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore and Molecular Docking-Based Virtual Screening of B-Cell Lymphoma 2 (BCL 2) Inhibitor from Zinc Natural Database as Anti-Small Cell Lung Cancer

Abstract: Cancer is a disease involving genetic factors in its pathogenesis. The increase of cell survival as a result of genetic changes, which prevent apoptosis such as Bcl2 (B-cell lymphoma-2) activation, will cause the tumor to grow. The overexpression of Bcl2 in small cell lung cancer should be inhibited. This study aims to screen natural products that can inhibit Bcl2 overexpression in lung cancer using pharmacophore- and molecular docking-based virtual screening to ZINC Natural Product database. The validation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Visualization of docking poses and interacting were carried out by using the Discovery Studio Visualizer [24]. Preparation of macromolecule and ligands, as well as docking studies, were carried out using AutoDock 4.2 [25][26][27] and exploring ligand stability in protein crystal structures was carried out using Amber18 [28].…”
Section: Hardware and Softwarementioning
confidence: 99%
“…Visualization of docking poses and interacting were carried out by using the Discovery Studio Visualizer [24]. Preparation of macromolecule and ligands, as well as docking studies, were carried out using AutoDock 4.2 [25][26][27] and exploring ligand stability in protein crystal structures was carried out using Amber18 [28].…”
Section: Hardware and Softwarementioning
confidence: 99%
“…The docking result was analyzed by observing the free binding energy of each ligand. The more negative free binding energy, the stronger the affinity of the ligand with the protein [22]. It means that ligands with smaller free binding energy than native ligands indicated that their affinity to the protein was better than the native ligand.…”
Section: Resultsmentioning
confidence: 99%
“…In order to get the best compound, the screening results of target compounds obtained from the molecular docking were further analyzed by observing the values of the smallest binding energy. The test compounds which have lower binding energy values than native ligand indicated that the binding strength of those compounds to the receptor was better (Muttaqin et al, 2020). In addition, the analysis was also performed by observing the interactions that occur between ligands and amino acids residues in receptors.…”
Section: Molecular Docking-based Virtual Screeningmentioning
confidence: 99%